Design of Fibre Ni/CGO Anode and Model Interpretation. (10th July 2019) - Ouyang, Mengzheng; Bertei, Antonio; Cooper, Samuel J; Wu, Yufei; Liu, Xinhua; Boldrin, Paul; Kishimoto, Masashi; Wu, Billy; Brandon, Nigel P
Abstract : A new structure of Ni/gadolinium-doped ceria (CGO) is prepared by a highly tuneable and facile combination of electrospinning and tape-casting method. The structure consists of a network made by continuous Ni fibres and filled in with CGO matrices. When used as the anode of solid oxide fuel cell (SOFC), though it has a lower triple phase boundary (TPB) density, it exhibits better performance compared with impregnated and cermet Ni/CGO with higher nickel loading. An algorithm is developed to determine the ceria-pore double phase boundary (DPB) density with different distance from nickel phase. Using the results, the relative electrochemical reaction rate on DPB and TPB of three different electrodes are calculated and proves that fibre-matrices structure has the morphology advantage of efficiently making use of all ceria-pore DPB. The relative contribution of DPB and TPB in anode reaction of SOFC is quantified in the first time and the importance of DPB is further stressed. This work provides new inspirations in material design of SOFC/SOEC and develops a novel strategy to evaluate the performance of electrodes quantitatively.